Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

for how many integers \(m\) the expression\[1+m+m^2+m^3+m^4\]becomes a perfect square?

Meta-math
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

1+m+m^2(1+m+m^2) \[1+m+m ^{2}(m+1)^{2}\]
sry
it will be perfect square for m=0 only

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Well, numerically I find others m not zero, m=-1,m=0 and m=3. A more rigorous proof is needed for all m in integers.
1+m(m+1)+m^3(m+1)=1+(m+1)(m+m^3) =1+(m+1)(m^2(m+1)) =1+(m^2)*(m+1)^2 =1+(m(m+1))^2 except zero it will not be a perfect square bcoz after sqauring 1is added which makes it a perfect square
you have done a mistake in your 2nd step @gorvs
sryyyyyyyyyyyy
all you are off line, I can write whatever I like, I choose (m^2 +1) ^2 as my perfect square, so \[(m^2+1)^2=m^4+2m^2+1\] to find out the solution, I let \[m^4+2m^2+1=m^4+m^3+m^2+m+1\] so, when \[m^2=m+m^3\], I have perfect square \[m^2=m^2(\frac{1}{m}+m)\] ---> \[\frac{1}{m}+m=1\] \[m^2-m+1=0\]no real solution for this.
I got a method but not too sure if its ideal lets take 1+ m + m^2 + m^3 + m^4 = p^2 for some integer p then m(1+m) + m^3 (1+m) = (p+1) (p-1) m(1+m)(1+m^2) = (p+1)(p-1).1 now comparing will get our answers, but it'll be bit lengthy as too many permutations possible like this one yields m=3 and p=11 m(1+m) = 1+p (1+m^2) = p-1 like wise we will make all possible comparisons and try to find out integer solutions
i asked you this before @mukushla
really, i cant remember, nice one :)
so do u know complete solution now?
well somehow i gave up and jus considered the fact that it is between two perfect squares so m=3
1 Attachment

Not the answer you are looking for?

Search for more explanations.

Ask your own question